E-Governance and University Performance: The Mediating Role of Service Quality, Innovation Quality, and Operational Quality at State Islamic Universities in Indonesia - Yusuf Amrozi; Fahma Wijayanti; M. Ainul Yaqin; Jumaiyah; Hasnan Abiyyu (Fundamental and Applied Management Journal, 2026)
Electronic governance (E-Governance) is increasingly positioned as the institutional backbone of universities in Indonesia navigating the transformation toward Legal Entity University status (PTN-BH). Yet precisely how digital governance investment translates into measurable university performance remains theoretically underexplored in Islamic higher education contexts. This study interrogates that question by applying DeLone and McLean's Information Systems Success Model adapted to the PTN-BH setting at UIN Sunan Ampel Surabaya, using Structural Equation Modeling (SEM) with 250 respondents drawn from the academic community. The findings reveal a selective and indirect influence pattern: E-Governance does not elevate performance directly, nor does service quality though significantly improved by digital governance function as a meaningful performance bridge. Instead, the pathway from electronic governance to institutional excellence runs specifically through innovation quality and operational quality, which serve as the genuine performance levers in the PTN-BH transition landscape. This pattern reframes the logic of digital governance investment in higher education: advancing e-governance alone is insufficient; its impact on performance depends on which quality dimension absorbs and transmits the governance improvement. For university administrators and policymakers, the implication is clear digital transformation agendas for PTN-BH aspirants must be strategically anchored in strengthening research capacity and operational efficiency, rather than solely targeting service delivery improvements.